Loss-of-function mutations in FREM2 disrupt eye morphogenesis. (April 2019) - Zhang, Xiayin; Wang, Dongni; Dongye, Meimei; Zhu, Yi; Chen, Chuan; Wang, Ruixin; Long, Erping; Liu, Zhenzhen; Wu, Xiaohang; Lin, Duoru; Chen, Jingjing; Lin, Zhuoling; et al.
Abstract: Cryptophthalmos is a rare congenital disorder characterized by ocular dysplasia with eyelid malformation. Complete cryptophthalmos is characterized by the presence of continuous skin from the forehead over the eyes and onto the cheek, along with complete fusion of the eyelids. In the present study, we characterized the clinical manifestations of three patients with isolated bilateral cryptophthalmos. These patients shared the same c.6499C > T missense mutation in the FRAS1-related extracellular matrix protein 2 (FREM2) gene, while each individual presented an additional nonsense mutation in the same gene (Patient #1, c.2206C > T; Patient #2, c.5309G > A; and Patient #3, c.4063C > T). Then, we used CRISPR/Cas9 to generate mice carrying Frem2 R725X/R2156W compound heterozygous mutations, and showed that these mice recapitulated the human isolated cryptophthalmos phenotype. We detected FREM2 expression in the outer plexiform layer of the retina for the first time in the cryptophthalmic eyes, and the levels were comparable to the wild-type mice. Moreover, a set of different expressed genes that may contribute secondarily to the phenotypes were identified by performing RNA sequencing (RNA-seq) of the fetal Frem2 mutant mice. Our findings extend the spectrum of FREM2 mutations, and provide insights into opportunities for the prenatal diagnosis of isolated cryptophthalmos. Furthermore, our work highlights the importance of the FREM2 protein during the development of eyelids and the anterior segment of the eyeballs, establishes a suitable animal model for studying epithelial reopening during eyelid development and serves as a valuable reference for further mechanistic studies of the pathogenesis of isolated cryptophthalmos. Highlights: Novel compound heterozygous mutations of FREM2 in three patients with rare bilateral cryptophthalmos. Recapitulates this complete cryptophthalmos phenotype in Frem2 R725X/R2156W mutant mice on a C57BL/6 background. The first description of FREM2 expression in the retina was completed. Data source for a set of genes which may contribute secondarily to the phenotypes. Evidence for FREM2 playing a critical role during the development of eyelids and the anterior segment of the eyeballs. Abstract : FREM2 playing a critical role during the development of eyelids and the anterior segment of the eyeballs.